Sensitivity enhancing injection from a sample reservoir and channel interface in microchip electrophoresis. Issue 4 (5th January 2017) - Wuethrich, Alain; Quirino, Joselito P.
Abstract : The stacking of a cationic analyte (i.e., rhodamine B) at the interface between a sample reservoir and channel in a microchip electrophoresis device is described for the first time. Stacking at negative polarity was by micelle to solvent stacking where the dye was prepared in a micellar solution (5 mM sodium dodecyl sulfate in 25 mM phosphoric acid, pH 2.5) and the channel was filled with high methanol content background solution (70% methanol in 50 mM phosphoric acid, pH 2.5). The injection of the stacked dye into the channel was by simple reversal of the voltage polarity with the sample solution and background solution at the anodic and cathodic reservoirs of the straight channel, respectively. The enrichment of rhodamine B at the interface and injection of the stacked dye into the channel was clearly visualized using an inverted fluorescence microscope. A notable sensitivity enhancement factor of up to 150 was achieved after 2 min at 1 kV of micelle to solvent stacking. The proposed technique will be useful as a concentration step for analyte mixtures in simple and classical cross‐channel microchip electrophoresis devices or for the controlled delivery of enriched reagents or analytes as narrow plugs in advanced microchip electrophoresis devices.